Pengaruh Promosi Online Terhadap Keputusan Konsumen Pada Pembelian Kosmetik di Online Shop - J, Jumawan; Nugroho, Aditya Aji; Kambuno, Lola; Melani, Putri Ayu Shayekti; Aprilia, Tantri; Putri, Zizka Amelia (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Promotion is a marketing strategy that attempts to encourage demand. Promotion is the company's main means of introducing products in a marketing strategy process. There are many media that can be used today to promote products, for example online promotions based on social media, websites, and e-commerce applications. There are many factors that can encourage consumers to make decisions to buy products, including online promotional strategies for consumer decisions regarding purchasing cosmetics, especially in online shops. This research aims to determine the effect of online promotions on consumer decisions when purchasing cosmetics in online shops. This research uses qualitative methods and searches for data and collects data from previous research as reference material. The results of this research show that online promotions have a significant effect on consumer decisions to purchase cosmetics in online shops. Therefore, companies that sell cosmetics can improve their online promotion-based promotional strategies to get more profitable results.